An empirical study on possible consequences of implementing offshore information technology outsourcing strategy. (1st December 2014) - Mukherjee, Santanu; Mukherjee, Kampan
Offshore information technology outsourcing (ITO) is one of the crucial strategic decisions pertaining to both the service provider and the client organisations. In light of the recent political clamour against the offshore ITO, it is quite logical for the decision–makers to reconsider all the established perceptions relating to its positive and negative consequences on the various stakeholders. The key issue in this debate is the worthiness of offshore ITO from the perspectives of both the contractual parties involved. Therefore, the intention of this article is to explore some specific parameters with the help of an empirical study to assess the benefits and possible challenges of offshore ITO. Although the study is based on the provider side perspectives, it helps discover two sets of factors, which not only explain various facets of offshore ITO outcomes but may help enhance the long–term visibility of its benefits and negative consequences from decision–makers' standpoint.